SOCIOECONOMIC STATUS AND LIVELIHOOD OF FISHER WOMEN OF HOOGHLY ESTUARY - ROY, APARNA; PANDIT, ARUN; SHARMA, A. P.; BHAUMIK, UTPAL; MAJUMDER, SUCHETA; BISWAS, DIPAK (Journal of the Inland Fisheries Society of India, 2021)
The analysis of age structure of fisher women showed that 35-55 years age groups are mainly engaged in various fishery related activities (50%) in average of total population. The average family size is 6, and 51.5% being the illiterate group. About 15% of the population are migrant having immigration from Bangladesh. Undernutrition and malnutrition are quite prevalent among the fisherwomen. The fisher women earn more than fifty percent (58%) of their livelihood from fisheries and related activities. Mass media exposure and extension contact of the fisher women both in freshwater and marine stretch was very low. Most of the fisherwomen perceive (81%) that lack of credit facilities from the Banks, Co-operatives etc is the major constraint. In most of the cases fisherwomen are not aware of the facilities offered by the State and Central Governments. Launching of mass literacy campaigns particularly for fisherwomen are much needed. Formation of SHGs, Mahila Mandal to upgrade their knowledge and skill is suggested. Key words: Fisher women, socio-economics, livelihood, Hooghly estuary